The Influence of Money Political Culture in Elections on the Sustainability of Indonesian Democracy - Simatupang, Jonasmer; Subekhan, Muhammad (Law Research Review Quarterly, 2018)
The purpose of this writing is motivated by the rise of money politics that occurs in almost every corner of the regions in Indonesia. Democracy is a system that is built where the people are given the absolute right to be given politically who is given the power to govern through the election process. The political dynamics can be seen through the democratic party in Indonesia. One of the challenges in the democratic party, through elections is the practice of money politics. Money politics takes place at every level of elections in Indonesia, which starts from the central level to the lowest level, namely the village. Money politics or money politics is an illegal practice in elections that can influence election participants with the lure of certain rewards and seems to have strong legitimacy from the people. People who have registered to participate in the election whether they participate in voting, or abstentions and vote because of money politics. This negative phenomenon arises in Indonesia's democratic transition. The process of money politics occurs due to the lack of regular supervision and outreach from the Election Supervisory Body, so that the elites or timses of political parties are free to do "generosity" when the day of D or before the election is held. In this regard, elections play a central role in Indonesia's democratic system. In several analyzes and studies, the Indonesian people still consider "reasonable" money politics conducted by election participants.